Hyperoside Attenuates Bleomycin-Induced Pulmonary Fibrosis Development in Mice - Huang, Jizhen; Tong, Xiang; Zhang, Li; Zhang, Yuan; Wang, Lei; Wang, Dongguang; Zhang, Shijie; Fan, Hong (Frontiers in Pharmacology, 2020)
Idiopathic pulmonary fibrosis (IPF) is a progressive, lethal and chronic lung disease. There are no effective drug therapies for IPF. Hyperoside, a flavonoid glycoside, has been proven to have anti-inflammatory, anti-fibrosis, antioxidant and anti-cancer effects. The aim of this study was to explore the role of hyperoside in bleomycin-induced pulmonary fibrosis development in mice. We established the pulmonary fibrosis model by a single intratracheal aerosol injection of bleomycin. Seven days after the bleomycin treatment, the mice were intraperitoneally administered with hyperoside for 14 days. We found that hyperoside treatment ameliorated fibrotic pathological changes and collagen deposition in the lungs of mice with bleomycin-induced pulmonary fibrosis. Hyperoside treatment also reduced the levels of MDA, TNF-α and IL-6 and increased the activity of SOD. In addition, hyperoside might inhibit the epithelial-mesenchymal transition (EMT) via the AKT/GSK3β pathway. Based on these findings, Hyperoside attenuated pulmonary fibrosis development by inhibiting oxidative stress, inflammation and EMT in the lung tissues of mice with pulmonary ﬁbrosis. Therefore, hyperoside might be a promising candidate drug for the treatment of pulmonary fibrosis.